94.3k views
4 votes
Helppppppppppppppppppppppppp

Helppppppppppppppppppppppppp-example-1
User Manojadams
by
5.1k points

1 Answer

4 votes

Answer:

Option A

Explanation:

We know that for an eqn.
ax^(2) +bx+c=0 , the quadratic formula is =


x = \frac{-b+\sqrt{b^(2)-4ac } }{2a} or \frac{-b-\sqrt{b^(2)-4ac } }{2a}

So using quadratic eqn. for
x^(2) -6x-5=0


x =\frac{-(-6)+\sqrt{(-6)^(2)-4*1*(-5) } }{2*1}or\frac{-(-6)-\sqrt{(-6)^(2)-4*1*(-5) } }{2*1}


=> x = (6+√(36+20) )/(2) or(6-√(36+20) )/(2)


=>x = (6+√(56) )/(2) or(6-√(56) )/(2)

User Adrian Preuss
by
4.7k points